O DEBATE PARLAMENTAR NA TRAMITAÇÃO DA LEI 10.639/2003: INTERROGANDO O PAPEL DA ESCOLA NA CONSTRUÇÃO DA EDENTIDADE CULTURAL E ÉTNICA NO BRASIL - Maria do Carmo Xavier; Ana Paula Lacerda Dornelles (EccoS – Revista Científica)
This paper proposes a reflection on the Law 10.639/03, given the lack of parliamentary debate on the significance of education in the construction of cultural and ethnic identity in Brazil. The objective is to confront the history teaching and Afro-Brazilian culture in the curriculum of elementary and secondary education as a strategy to fight for social inclusion of the black. The text contributes to clarify the positions of speech of the subjects involved in this debate and allows to contextualize the challenges in the production of public policies aimed at correcting social inequalities on the Brazilian scenario.